Fertilizer nitrogen and stover removal effects on sorghum yields and nutrient uptake and partitioning - Powell, J.M.; Hons, F.M. (Elsevier, 1992)
A four year field study was conducted in central Texas to evaluate the effects of sorghum (Sorghum bicolor L. Moench) genotype, fertilizer N application rate and stover removal on crop yields and plant nutrient uptake and partitioning. Fertilizer N application rates of 112 kg ha were generally sufficient to produce maximum yields, to attain the highest fertilizer N application rate and the amounts of N, P and K taken up by grain and forage sorghum cultivars. A strong interdependence between fertilizer N application rate and stover return on nutrient cycling appeared to be developing in the cropping system under the study. Stover removal adversely affected yields, nutrient uptake and partitioning during the last 2 study areas.